2017
DOI: 10.1111/phpp.12290
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet A eye irradiation ameliorates colon carcinoma induced by azoxymethane and dextran sodium sulfate through β‐endorphin and methionine‐enkephalin

Abstract: These results suggested that UVA eye irradiation exerts major effects on AOM + DSS-induced colon carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…The increase in ACTH secretion was most marked in mice with symptoms of AD (data not shown). ACTH has been shown to increase the expression of TSLP through the activity of nucleotide‐binding domain, leucine‐rich‐containing family, pyrin domain‐containing‐3 protein , and AD progression is thought to occur via this mechanism. However, we have previously reported that symptoms of DSS‐induced ulcerative colitis and AOM + DSS‐induced colon cancer can be ameliorated by UVA eye irradiation .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase in ACTH secretion was most marked in mice with symptoms of AD (data not shown). ACTH has been shown to increase the expression of TSLP through the activity of nucleotide‐binding domain, leucine‐rich‐containing family, pyrin domain‐containing‐3 protein , and AD progression is thought to occur via this mechanism. However, we have previously reported that symptoms of DSS‐induced ulcerative colitis and AOM + DSS‐induced colon cancer can be ameliorated by UVA eye irradiation .…”
Section: Discussionmentioning
confidence: 99%
“…ACTH has been shown to increase the expression of TSLP through the activity of nucleotide‐binding domain, leucine‐rich‐containing family, pyrin domain‐containing‐3 protein , and AD progression is thought to occur via this mechanism. However, we have previously reported that symptoms of DSS‐induced ulcerative colitis and AOM + DSS‐induced colon cancer can be ameliorated by UVA eye irradiation . We have now also shown that AD symptoms can be reduced by UVA eye irradiation, suggesting a role for clock genes and the circadian rhythm in the progression of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a mouse model of colon carcinoma induced by azoxymethane and dextran sodium sulphate, UVA radiation exposure of the eye resulted in elevated β-END and methionine-enkephalin, upregulation of their respective receptors, decreased IL-6 and TNF-α ( tumor promoters during early colitis-associated carcinogenesis), increased apoptosis markers and decreased cell proliferation markers compared to control. 257 The authors concluded that UVA irradiation of the murine eye was able to ameliorate symptoms of colon carcinoma through upregulation of β-END and methionine-enkephalin. Another experiment exposed the back skin of mice to UVB radiation and found that levels of CRH, β-END, ACTH and corticosterone were enhanced.…”
Section: Endorphin (β-End) and Adrenocorticotropic Hormone (Acth)mentioning
confidence: 99%
“…This experiment also showed a downregulation of the number of epidermal LCs in epidermal sheets derived from the ear and upregulation of secretory IgA in the gut, which indicates that systemic modulation of downstream organs may be plausible after UVA exposure to the eye. In a mouse model of colon carcinoma induced by azoxymethane and dextran sodium sulphate, UVA radiation exposure of the eye resulted in elevated β‐END and methionine‐enkephalin, upregulation of their respective receptors, decreased IL‐6 and TNF‐α ( tumor promoters during early colitis‐associated carcinogenesis), increased apoptosis markers and decreased cell proliferation markers compared to control 257 . The authors concluded that UVA irradiation of the murine eye was able to ameliorate symptoms of colon carcinoma through upregulation of β‐END and methionine‐enkephalin.…”
Section: Proopiomelanocortin (Pomc) Alpha‐melanocyte Stimulating Hormone (α‐Msh) Beta‐endorphin (β‐End) and Adrenocorticotropic Hormone (mentioning
confidence: 99%